Synthesis and magnetism of hierarchical iron oxide particles. (5th December 2015) - Long, Nguyen Viet; Yang, Yong; Teranishi, Toshiharu; Thi, Cao Minh; Cao, Yanqin; Nogami, Masayuki
Abstract: The hierarchical polyhedral α-Fe2 O3 oxide particles, and hierarchical spherical CoFe2 O4 oxide particles in the microsized ranges have been successfully prepared via modified polyol methods with NaBH4 and heat treatment process. An exact comparison was presented in the soft magnetic properties and structures of new hierarchical α-Fe2 O3 and CoFe2 O4 oxide particles. To study Fe-based oxide microparticles, X-ray diffraction, scanning electron microscopy with energy dispersive spectroscopy, X-ray photoelectron spectroscopy, and vibrating sample magnetometer have been used to characterize their microstructures and magnetic properties according to the preparation processes. The hierarchical α-Fe2 O3 and CoFe2 O4 oxide microparticles with oxide grain and grain boundary textures were perfectly formed under heat treatment at high temperature without any chemical self-assembly methods. For this exciting research, the various kinds of homogeneous hierarchical Fe-based oxide particles can be successfully produced in the large amount for commercialization. It is discovered that MS of hierarchical CoFe2 O4 particles is much larger than that of hierarchical α-Fe2 O3 particles about 93 times. The coordination numbers of Co and Fe cations at tetrahedral and octahedral sites lead to determine its magnetic behavior. Finally, hierarchical Fe-based oxide particles are proposed for promising and potential candidates for energy and environment related technologies associated with safety and sustainability. Graphical abstract: Highlights: α-Fe2 O3 and CoFe2 O4 particles are prepared by NaBH4 and heat treatment. New evidence of formation of grain and grain boundary in magnetic oxide particles High heat treatment is proposed for magnetic particles of grain and grain boundary. Magnetic particles have good coercive field and high saturation magnetization.